The Linkages Between Stock Return And Macroeconomic Variables In Malaysia - Phang, Chee Kong (2006)
The objective of this study is to examine the relationship between stock return and macroeconomic variables in Malaysia. Cointegration test is used to examine the existence of long run relationship between stock return and macroeconomic variables. Besides, Granger causality test is also used to study the causal relationship between stock return and macroeconomic variables. In order to understand if there is any changes in the relationship on pre and post capital control period, the data is divided into pre capital control (1990 Q 1 to 1998 Q3) and post capital control ( 1998 Q4 to 2004 Q4) period. Cointegration test suggest the existence of long run relation between stock return and all the macroeconomic variables considered in the study, for the period before and after the implementation of capital control. The Granger causality test suggests bidirectional causal relationship between Kuala Lumpur Composite Index and macroeconomic before capital control, and unidirectional causality from macroeconomic variables to Kuala Lumpur Composite Index after capital control. The Granger causality test also suggests Second Board Index Granger causes macroeconomic variables before and after capital control.